Magnolol inhibits growth and induces apoptosis in esophagus cancer KYSE-150 cell lines via the MAP kinase pathway - Chen, Yu; Huang, Kenan; Ding, Xinyu; Tang, Hua; Xu, Zhifei (Journal of Thoracic Disease, 2019)
Background: Magnolol has shown anti-cancer activity against a variety of cancers, such as liver, breast, lung and colon cancer. However, the role of magnolol in esophagus cancer cells is unknown. Methods: In this study, esophagus cancer cell lines including TE-1, Eca-109 and KYSE-150 were used to evaluate the cytotoxic effect of magnolol on cell proliferation, apoptosis and migration. Results: We found that magnolol inhibits cellular proliferation of all three cell lines in a time- and dose-dependent manner; 20 µM magnolol markedly inhibited the migration ability of KYSE-150 cell which was accompanied with a decreased expression of MMP-2. Treatment with 100 μM magnolol significantly increased KYSE-150 cell apoptosis. We found that cleaved caspase-3, cleaved capsese-9 and Bax protein expression was increased and Bcl-2 protein expression was decreased after magnolol treatment. In addition, Magnolol had no effect on JNK but induced the phosphorylation of p38 and ERK1/2 in a concentration-dependent manner, suggesting the involvement of these kinases in the initiation of the apoptosis process. Finally, magnolol treatment significantly suppressed KYSE-150 tumor cell growth in nude mouse xenograft models. Conclusions: The results of this study provide a basis for the understanding and development of magnolol as a potential novel drug for esophagus cancer.